The TNF Superfamily Methods and Protocols - Bayry, Jagadeesh.; Bayry, Jagadeesh. (Methods in Molecular Biology, 2014)
Exploring these type II trans-membrane proteins, The TNF Superfamily: Methods and Protocols focuses on various techniques to investigate aspects of the TNF Superfamily members in health and disease. Opening with protocols to understand the signaling process of TNF family members, this detailed volume continues with technical examples of investigating the role of TNF family members in physiopathologies, protocols on modulation of TNF signaling by pathogens, experimental applications of TNF-reporter mice, as well as methodologies for various assays of TNF family members and the production of recombinant molecules.  Written for the Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and ready to use, The TNF Superfamily: Methods and Protocols will aid researchers investigating this key family of proteins, involved in vital processes such as providing signals for activation, differentiation, survival and death of cells, modulation of immune response and inflammation, hematopoiesis, and osteoclastogenesis.